FINANCIAL ATTITUDES DAN KOMUNIKASI KELUARGA TENTANG PENGELUARAN UANG SAKU : DITINJAU DARI PERBEDAAN GENDER - Utaminingsih, Retno; Rita, Maria Rio (Jurnal Manajemen dan Keuangan, 2010)
Previous researches showed that the range of financial attitudes of male and female are different. In addition, communication patterns between men and women also different, men have a tendency to be less open than women. On the one hand, there is research says that financial issues can trigger conflict affects families and personal lives and academic success. This study attempts to examine the problems using student of Faculty of Economics and Business Satya Wacana Christian University (n = 302). The results showed that there are differences in various financial attitudes between women and men, women and men have the same level of openness in family communication about spending their pocket money and financial attitudes owned by women and men can affect family communication about spending their pocket money.Keyword: Financial Attitudes, Family Communication, Gender